Caring for Caregivers: Exploring Physical Self-care Perspectives and Practices among Dental Students - Dur-e-Saman, Dur-e-Saman; Adeeb, Humera; Ayub, Uzair; Tahir, Momina; Nasir, Mariam; Shahid, Muhammad (Journal of Neonatal Surgery, 2025)
Background: The importance of self-care in medical education has been a major area of focus because self-care is one of the ways to eliminate burnout and enhance resilience in students. Although there has been an increase in global interest, there is a paucity of evidence regarding the perceptions and practices of dental students in Pakistan with regard to self-care in the academic and socio-cultural setting. Objective: This paper has examined the views, habits, and contextual factors that shape self-care behaviors among both male and female dental students in Abbottabad in Pakistan. Methods: The lived experiences of ten undergraduate students studying the Bachelor of Dental Surgery (BDS) at various institutions were studied using a qualitative phenomenological approach. The interviews were carried out between June and October 2025 and were semi-structured. The thematic analysis of data relied on the six-phase framework of Braun and Clarke, which was based on the socio-ecological model to place the results of the study into the context of personal, interpersonal, institutional, and environmental levels. Results: Six themes emerged: (1) academic pressure as a structural barrier to self-care, (2) sociocultural and gender influences restricting physical activity, (3) family as both a source of support and constraint, (4) peer influence reinforcing an overwork culture, (5) awareness of self-care without sustained behavior, and (6) environmental and policy supports for student wellness. While students demonstrated awareness of healthy habits such as exercise, diet and rest, systemic academic demands, cultural expectations, and lack of institutional wellness initiatives hindered consistent practice. Conclusion: Dental students of medical and dental colleges in Abbottabad view self-care as a necessity, but there are structural, cultural, and behavioral challenges that restrict its application. A culture of self-care within medical education can be reinforced by incorporating structured wellness, culturally competent, gender-inclusive policies, and faculty as role models of healthy behaviors into the medical educational curriculum.